The Implementation of Jigsaw Type of Cooperative Learning to Improve Students’ Motivation and Learning Outcomes - Tukiyantini, Sri (Universitas Pahlawan Tuanku Tambusai, 2023)
Low student learning motivation can have an impact on decreasing student learning outcomes. So it takes applying a special learning model to increase student motivation. Therefore, this study aims to increase student motivation and learning outcomes through the Jigsaw cooperative learning model. This study uses classroom action research adopted from the Kemmis and McTaggart models. Four stages of research have been used in these two research cycles. A total of 34 class XI students were involved as research respondents. Student motivation was assessed using observation sheets, and learning outcomes were assessed using multiple-choice tests. Motivational data and student learning outcomes were analyzed using percentage techniques. Motivation and student learning outcomes increased significantly after two cycles of action. Student motivation increased from 66.25% in cycle 1 to 80.63% in cycle 2. Meanwhile, student learning outcomes increased from 73.03 in cycle 1 to 82.26 in cycle 2. So, it can be concluded that the application of the cooperative learning model Jigsaw is effective in increasing student motivation and learning outcomes.